(untitled) (Research, Society and Development, 2022)
Social isolation as a measure to contain the growth of cases of people infected by the covid-19 pandemic has caused profound changes in human experiences, which also implies as in the educational context. This Experience Report presents the narrative of a young teacher who is currently also a master’s student in Psychology from the Bahian School of Medicine and Public Health. The objective of this narrative is to describe and analyze the perception of experience of teaching practice during the period of covid-19 and its implications in teaching as well as in the relations established with students in the university, from the understanding of an engaged pedagogy. I conclude that the experience of this report is not finished here, because I believe that new processes of reflection, tensions and new opportunities to discover can happen. It is considered that the pandemic of the new coronavirus has had an impact on the various areas of human experience, including education as well as in the relationships that occurred in this context where the teacher and the student are fundamental pieces.